2005
DOI: 10.1108/02635570510592343
|View full text |Cite
|
Sign up to set email alerts
|

Internet banking: strategic responses to the accession of WTO by Chinese banks

Abstract: PurposeTo assess to what extent Chinese domestic banks' use of internet banking as a strategic response to the entrance of the WTO is affected by factors both external and internal to the banks.Design/methodology/approachA model depicted by a path diagram is developed to test the impact of various external and internal factors considered to have an impact on Chinese domestic banks' strategic response to the accession into the WTO. Survey questions from prior studies were adopted and modified. Structural equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 20 publications
2
32
1
Order By: Relevance
“…This result confirms previous authors' findings (Lu et al 2005, Zhao et al, 2010, Kim et al, 2008, Chang and Chen, 2008. The more an individual trusts a website the bigger is his intention to purchase on this website.…”
Section: Discussionsupporting
confidence: 93%
“…This result confirms previous authors' findings (Lu et al 2005, Zhao et al, 2010, Kim et al, 2008, Chang and Chen, 2008. The more an individual trusts a website the bigger is his intention to purchase on this website.…”
Section: Discussionsupporting
confidence: 93%
“…By gaining an in-depth understanding of the factors and conditions that influence developing country's ability to fully adopt and realise its benefits, strategic implications can be generated for the researchers and practitioners regarding how to promote the growth of e-banking in the developing countries. However, despite the importance of these adoption studies in developing countries, limited studies are currently available [3,4,7,8]. Therefore, more studies are still required to understand the relevance of ebanking in developing countries and to identify areas the developing countries lag behind which inhibit their e-banking adoption and diffusion.…”
Section: Introductionmentioning
confidence: 94%
“…Firstly, Chinese banking industry is not generally well understood since it had enjoyed a strong government protection from foreign competitors over a long period of time [4]. Currently, there are still limited studies about the adoption of e-banking by Chinese domestic banks [7]. Choosing one of the big four stateowned domestic banks reflects the mainstream banking practices in China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research of Akinci et al indicated that regarding consumers' attitudes and adoption of e-banking, there were significant differences between e-banking users and non-e-banking users in terms of attitudinal properties, demographic profiles, and preferences for service delivery channels. Lu, Liu, Jing, and Huang (2005) revealed that China's entrance into the WTO makes the banking environment more competitive. While above these papers presented that internet banking has been widely applied and highly recognized in some countries, relatively little of the research has emphasized the impact of internet banking adoption on the banking industry in China.…”
Section: Proposed Hypothesismentioning
confidence: 99%